The Excavation of the Shrine of Apollo at Nettleton, Wiltshire, 1956-1971 - Wedlake, W.J (Reports of the Research Committee of the Society of Antiquaries of London, 1982)
This is a report on the excavation of the Shrine of Apollo at Nettleton, in Wiltshire, England, between 1956 and 1971. Included are descriptions of artefacts such as pottery, coins and buildings, together with an account of the methodology used to unearth these.